Digital imitation of batik, tie-dye and weave effects for manual screen printing. (6th December 2022) - Howard, Ebenezer Kofi; Asinyo, Benjamin Kwablah; Seidu, Raphael Kanyire; Amankwah, Akosua Mawuse; Chichi, Cynthia Akua; Anyan, Portia
Batik, tie-dye and woven structures are special fabrics that have significant numbers of interesting designs and patterns cherished by most consumers. Despite these, it is observed that producers have issues with their mode of production. Notably, the material and chemicals used, such as wax, sodium hydrosulphite and caustic soda for batik/tie-dye, are harmful to humans, causing suffocation when inhaled and posing serious health issues to producers and users. This study explored the possibility of replicating the batik, tie-dye and woven structure effects through hand screen printing, a versatile and relatively easy technique for patterning fabrics. Art studio-based experimental and observation approaches were used. The results revealed feasible and unique surface textile patterns closely resembling batik, tie-dye and weave effects. The study recommends the exploration of this novel concept for practitioners in patterning fabrics to reduce the time and health challenges that come with the production process.